1997
DOI: 10.1073/pnas.94.8.3584
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Lyme disease antigen outer surface protein A complexed with an Fab

Abstract: OspA (outer surface protein A) is an abundant immunogenic lipoprotein of the Lyme disease spirochete Borrelia burgdorferi. The crystal structure of a soluble recombinant form of OspA was solved in a complex with the Fab fragment of mouse monoclonal antibody 184.1 and refined to a resolution of 1.9 Å. OspA has a repetitive antiparallel ␤ topology with an unusual nonglobular region of ''freestanding'' sheet connecting globular N-and C-terminal domains. Arrays of residues with alternating charges are a predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
163
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 52 publications
5
163
1
Order By: Relevance
“…Epitopes on OspA that bind borreliacidal Abs vs those that bind tick gut epithelium are likely to be different. Mapping studies have shown that protective OspA mAbs, such as LA-2 and C3.78 bind to conformational epitopes within the carboxyl terminus of OspA (25,35). At least one of the epitopes that …”
Section: Discussionmentioning
confidence: 99%
“…Epitopes on OspA that bind borreliacidal Abs vs those that bind tick gut epithelium are likely to be different. Mapping studies have shown that protective OspA mAbs, such as LA-2 and C3.78 bind to conformational epitopes within the carboxyl terminus of OspA (25,35). At least one of the epitopes that …”
Section: Discussionmentioning
confidence: 99%
“…However, the standards used to calibrate the column were typical globular proteins. OspB, which is 53% homologous to OspA (6), probably exists as a dumbbell-shaped protein (N-and C-terminal globular domains connected by a single-layer ␤ sheet) as has been shown for OspA (49,50). Therefore, the size estimated for B31-tOspB using globular proteins as reference represents an overestimate.…”
Section: Discussionmentioning
confidence: 83%
“…Still, putative structural similarity between HpaA and ospA can be interesting even today because vaccines based on ospA were shown to induce protective immunity. 44 Overall sequence similarity between the two proteins is supplemented by substantial residue conservation in the cleft that is present in the C-terminal part of ospA. This cleft contains several hydrophobic and partly buried charged residues that are conserved in HpaA.…”
Section: Predictions For Proteins Of Known or Putative Functionmentioning
confidence: 99%
“…The flagellar sheath protein HpaA is predicted with a very high score to have the structure of outer surface protein A (ospA), an antigen of the Lyme disease spirochete. 44 Both proteins are lipoproteins of unknown functions 45 ; therefore, the present prediction could be more useful in the future when the function of one of them is discovered. Still, putative structural similarity between HpaA and ospA can be interesting even today because vaccines based on ospA were shown to induce protective immunity.…”
Section: Predictions For Proteins Of Known or Putative Functionmentioning
confidence: 99%
See 1 more Smart Citation